طُرُقُ حَدِيْثُ النَّبِيِ - عَلَيّهِ الصَّلَاةُ والسَّلَامُ - حِيْثُ كِانَ فِي الْحَائِطِ وَمَا فِي مَعْنِاهُ"، تحقيقُ ودراسةُ،للحافظ: ضِيَاءُ الدِّيْنِ ، أَبُو عَبْدِ اللهِ ، مُحَمَّدُ بنُ عَبْدِ الوَاحِدِ المَقْدِسِيُّ- رحمه الله -(المتوفى: 643هـ): تحقيق ودراسة - Balah, Abdurrahman Sayyed Abdul Ghofar (Jurnal Studi Al-Qur'an, 2022)
This study dealt with the realization of this manuscript, and this manuscript is an investigation of an essential part of my hadith, which is: “The paths of the hadith of the Prophet as it was on the wall and what is in its meaning”, by Al-Hafiz: Zia Al-Dha’i, the author of the various hadiths, in which the hadiths are collected from the various hadiths. The Prophet, peace be upon him when he was in the wall. His companions entered upon him and gave them good tidings of Paradise, so he mentioned it on the authority of ten of the companions of the Messenger of God, peace be upon him, with its chains of transmission, which are narrations: Bilal, Abu Musa, Abdullah bin Amr, Abdullah bin Omar, Anas, Abu Hurairah, and Zaid bin Arqam And Abdullah bin Masoud, Jaber bin Abdullah, and Abi Masoud Uqbah bin Amr - may God be pleased with them - all, and it contained 12 hadiths. Ibn Abbas, Zaid Ibn Thabit, and Abu Hudhayfa al-Ansari may God be pleased with them - and the researcher went in his research on the inductive, descriptive, analytical and critical method.